Light localization in one-dimensional photonic crystal heterostructures - Tanaue, Helena Borlina [UNESP]; Reyes-Gómez, Ernesto; Bruno-Alfonso, Alexys [UNESP] (Elsevier, 2021)
Effects of both metamaterial inclusion and lack of inversion symmetry on the localized modes in one-dimensional photonic heterostructures under normal incidence are investigated. Each structure consists of two semi-infinite photonic crystals separated by an interface or by several layers. A general condition for light localization between semi-infinite crystals is given by parallelism between two-dimensional vectors in the electromagnetic (H, E) space. The case of a defective photonic crystal is recovered by joining crystals having the same unit cell. The defect modes display leftward and rightward damped oscillations with the same ratio, even when the unit cell lacks inversion symmetry. Their frequencies are found in good agreement with peaks of the transmittance through truncated structures. In heterostructures including metamaterials, an anomalous exponential decay of the magnetic field is found near one edge of the zero-〈n〉 gap.
Keywords: Defect; Heterostructure; Localized modes; Metamaterial; Photonic crystal; Transfer-matrix method